Short-term regulation of hematopoiesis by lipoprotein(a) results in the production of pro-inflammatory monocytes. (15th September 2020) - Schnitzler, Johan G.; Poels, Kikkie; Stiekema, Lotte C.A.; Yeang, Calvin; Tsimikas, Sotirios; Kroon, Jeffrey; Stroes, Erik S.G.; Lutgens, Esther; Seijkens, Tom T.P.
Abstract: Background: Lipoproteins are important regulators of hematopoietic stem and progenitor cell (HSPC) biology, predominantly affecting myelopoiesis. Since myeloid cells, including monocytes and macrophages, promote the inflammatory response that propagates atherosclerosis, it is of interest whether the atherogenic low-density lipoprotein (LDL)-like particle lipoprotein(a) [Lp(a)] contributes to atherogenesis via stimulating myelopoiesis. Methods & results: To assess the effects of Lp(a)-priming on long-term HSPC behavior we transplanted BM of Lp(a) transgenic mice, that had been exposed to elevated levels of Lp(a), into lethally-irradiated C57Bl6 mice and hematopoietic reconstitution was analyzed. No differences in HSPC populations or circulating myeloid cells were detected ten weeks after transplantation. Likewise, in vitro stimulation of C57Bl6 BM cells for 24 h with Lp(a) did not affect colony formation, total cell numbers or myeloid populations 7 days later. To assess the effects of elevated levels of Lp(a) on myelopoiesis, C57Bl6 bone marrow (BM) cells were stimulated with lp(a) for 24 h, and a marked increase in granulocyte-monocyte progenitors, pro-inflammatory Ly6 high monocytes and macrophages was observed. Seven days of continuous exposure to Lp(a) increased colony formation and enhanced the formation of pro-inflammatory monocytes and macrophages. Antibody-mediated neutralization of oxidized phospholipids abolished the Lp(a)-induced effects on myelopoiesis. Conclusion: Lp(a) enhances the production of inflammatory monocytes at the bone marrow level but does not induce cell-intrinsic long-term priming of HSPCs. Given the short-term and direct nature of this effect, we postulate that Lp(a)-lowering treatment has the capacity to rapidly revert this multi-level inflammatory response. Highlights: Lp(a) does not induce intrinsic priming of hematopoietic stem and progenitor cells. Lp(a) enhances the production of inflammatory monocytes at the bone marrow level. Lp(a)-lowering treatment may rapidly revert this multi-level inflammatory response.